Antitumor activity of recombinant RGD-IFN-α2a-core fusion protein in vitro. Issue 1 (January 2017) - Wen, Zhengwei; Jia, Qunying; Kang, Xiaojuan; Lou, Yongliang; Zou, Lilin; Yang, Jifeng; Gao, Jimin; Han, Liping; Li, Xiang
Abstract : Interferon (IFN) regulates immune responses and antitumor activity. Arginine–glycine–aspartic acid (RGD) peptides can specifically bind to integrin αv β3, a transmembrane receptor that is highly expressed on the surface of various cancer cells. In this study, we expressed recombinant RGD-IFN-α2a-core fusion proteins and assessed their antitumor activity in vitro . Two RGD-IFN-α2a-core fusion proteins and a negative control protein were expressed in vitro . These two RGD-IFN-α2a-core fusion proteins could bind the tumor cell surface specifically and did not bind to normal cells. RGD-IFN-α2a-core fusion protein treatment of tumor cells significantly reduced cell viability and induced apoptosis in a dose-dependent manner. At the 'mRNA' level, both proteins could upregulate CASP3 expression. These data indicate that both laboratory-engineered RGD-IFN-α2a-core fusion proteins could bind the surface of tumor cells and induce apoptosis in vitro . Further studies will investigate the in-vivo antitumor activities of the RGD-IFN-α2a-core fusion proteins.